2019
DOI: 10.24090/jk.v7i1.2756
|View full text |Cite
|
Sign up to set email alerts
|

Manajemen Personalia Dalam Pemberdayaan Sekolah Di SMP Muslimin 5 Kota Bandung

Abstract: Abstrak Fakta-fakta di bidang program kerja di sekolah tidak berjalan mulus karena tugas dan tanggung jawab tidak diberikan kepada orang yang tepat. Jadi ini akan memadamkan potensi guru lain yang memiliki keahlian di bidangnya. Penelitian ini bertujuan untuk mengidentifikasi proses kepegawaian di SMP Muslim 5 di Kota Bandung, dan menganalisis proses pemberdayaan sekolah sehingga pendidik dan staf pendidikan dapat mengasah keterampilan mereka di bidang mereka lebih dalam. Hasil penelitian menunjukkan: 1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…The organizational structure in the teaching factory must also be clearly compiled with a description of the work of each member. It compiles the existing organizational structure at school to achieve the goals of school programs that have been designed so that the program can run effectively and efficiently (Nurmalasari & Syah, 2019). Job descriptions at the teaching factory of SMK SMTI Yogyakarta can be seen in Table 2.…”
Section: Organizational Structure and Job Descriptionmentioning
confidence: 99%
“…The organizational structure in the teaching factory must also be clearly compiled with a description of the work of each member. It compiles the existing organizational structure at school to achieve the goals of school programs that have been designed so that the program can run effectively and efficiently (Nurmalasari & Syah, 2019). Job descriptions at the teaching factory of SMK SMTI Yogyakarta can be seen in Table 2.…”
Section: Organizational Structure and Job Descriptionmentioning
confidence: 99%
“…Keputusan pembelian merupakan tindakan yang dilakukan konsumen untuk melakukan pembelian sebuah produk dan suatu proses pemilihan salah satu dari beberapa alternatif penyelesaian masalah dengan tindak lanjut yang nyata (Nurmalasari & Manajemen, 2017). Banyak faktor yang dapat mempengaruhi keputusan pembelian dalam suatu produk sangat dipengaruhi oleh penilaian kualitas produk dan harga tersebut (Zhang & Benyoucef, 2016), Promosi diharapkan memberikan pengaruh positif terhadap meningkatnya penjualan, promosi bukan saja berfungi sebagai alat komunikasi antara perusahaan dengan pelanggan, melainkan sebagai alat untuk mempengaruhi pelanggan (Ririn Tri Ratnasari, 2011).…”
Section: Pendahuluanunclassified
“…Ployhart revealed that staffing is a process of attracting, selecting and retaining competent workers to achieve organizational goals [5]. The staffing process aims to realize the synergy of workers in accordance with their duties and obligations, realize work that is cooperative, effective and integrated, makes it easier for workers to complete their duties because it suits their respective fields of expertise, and encourages workers to provide a maximum effort and results for the organization [6]. The stages of the staffing process according to Skidmore consist seven stages, there are: 1) Recruitment, 2) Selection, 3) Appointment, 4) Orientation, 5) Promotion, 6) Appraisal, and 7) Termination [4].…”
Section: Introductionmentioning
confidence: 99%